2022
DOI: 10.3390/biomedicines10071753
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Digital Analysis of Tissue Immune Components Reveals an Immunosuppressive and Anergic Immune Response with Relevant Prognostic Significance in Glioblastoma

Abstract: Objectives: Immunostimulatory therapies using immune checkpoint blockers show clinical activity in a subset of glioblastoma (GBM) patients. Several inhibitory mechanisms play a relevant role in the immune response to GBM. With the objective of analyzing the tumor immune microenvironment and its clinical significance, we quantified several relevant immune biomarkers. Design: We studied 76 primary (non-recurrent) GBMs with sufficient clinical follow-up, including a subgroup of patients treated with a dendritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In addition, lymphocyte infiltration in tumors is related to the superior prognosis of patients with cancer ( 31 ). Moreover, in a recent quantitative digital analysis, the researchers reported that high expressions of CD8+ and CD163+ cells were significantly connected with inferior survival in patients with GBM ( 32 ). According to their observations, a direct correlation was found between CD163 values and CD8 or PDL1/PD1 infiltration in patients with GBM ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lymphocyte infiltration in tumors is related to the superior prognosis of patients with cancer ( 31 ). Moreover, in a recent quantitative digital analysis, the researchers reported that high expressions of CD8+ and CD163+ cells were significantly connected with inferior survival in patients with GBM ( 32 ). According to their observations, a direct correlation was found between CD163 values and CD8 or PDL1/PD1 infiltration in patients with GBM ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent quantitative digital analysis, the researchers reported that high expressions of CD8+ and CD163+ cells were significantly connected with inferior survival in patients with GBM ( 32 ). According to their observations, a direct correlation was found between CD163 values and CD8 or PDL1/PD1 infiltration in patients with GBM ( 32 ). Therefore, the high SII value can be adopted for predicting the dismal prognosis of glioma cases.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of TAMs indicated a short survival time in patients with Gb. In the study of Idoate Gastearena et al ( 35 ), the median value of CD163+ TAMs was 10.48%. Based on this cutoff value, there was a negative correlation between CD163+ TAM infiltration and OS.…”
Section: Discussionmentioning
confidence: 93%
“…Reversal of this sequestering through immunotherapy has shown to be an effective adjunctive therapy ( 21 ). Additionally, increased expression of CD8+ cells and CD163+ cells have demonstrated to be correlated with worse survival and prognosis due to lymphocyte immunosuppression ( 32 , 39 ). Additionally, the GBM microenvironment includes glioma stem-like cells (GSCs) which evade immune therapies through multiple mechanisms including but not limited to the down regulation of MHC class I molecules, increasing Treg cells within the microenvironment, increasing TAM-produced TGF-β, and resulting down regulation of MHC II ( 40 ).…”
Section: Intrinsic Factors Of Resistance In Gbmmentioning
confidence: 99%